2018
DOI: 10.4236/ojn.2018.810057
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Clinical Practice Guidelines during Antenatal Management of Gestational Diabetes Mellitus: An Integrative Review

Abstract: The number of pregnant women affected by gestational Diabetes (GDM) is increasing globally with an estimated prevalence as high as 15%. Gestational Diabetes Miletus is associated with birth complications for women and newborn, includes development of type II diabetes, preeclampsia during pregnancy, increasing the risk of fetal loss, stillbirth and perinatal death. An integrative literature review applied, systematic search from different data base obtained from international and middle east countries to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
0
0
1
Order By: Relevance
“…Although internationally, guidelines on screening and management of GDM are available that may be used to guide midwives in their practices, these are not contextualized and translated to accommodate the Ghanaian context [ 9 ]. In line with the findings of an integrative review regarding clinical practice guidelines' adherence during the management of GDM [ 10 ], the researcher's observations at the time of the current study suggested that screening and nursing management of GDM in the antenatal, intra partum and postpartum periods in Ghana is often done inconsistently and not according to the latest evidence. Thus, a need was identified for developing evidence-based recommendations (hereafter referred to as ‘recommendations’) in order to assist midwives in providing evidence-based care regarding the screening and management of GDM in Ghana.…”
Section: Introductionsupporting
confidence: 60%
“…Although internationally, guidelines on screening and management of GDM are available that may be used to guide midwives in their practices, these are not contextualized and translated to accommodate the Ghanaian context [ 9 ]. In line with the findings of an integrative review regarding clinical practice guidelines' adherence during the management of GDM [ 10 ], the researcher's observations at the time of the current study suggested that screening and nursing management of GDM in the antenatal, intra partum and postpartum periods in Ghana is often done inconsistently and not according to the latest evidence. Thus, a need was identified for developing evidence-based recommendations (hereafter referred to as ‘recommendations’) in order to assist midwives in providing evidence-based care regarding the screening and management of GDM in Ghana.…”
Section: Introductionsupporting
confidence: 60%
“…El 2018, Nisreen I. y col. Jordania; investigaron Adherencia a las GPC durante el manejo prenatal de diabetes mellitus gestacional, encontrando adherencia completa del proveedor a pautas prenatales (48,1%) 7 . El 2018, Grisolle Ortiz y col. Colombia; reportan Adherencia a guías de atención de control prenatal, como media (86%) y aceptable (85.8%) adherencia 8 .…”
Section: Introductionunclassified